Docetaxel monotherapy induces necrotic acute pancreatitis. (September 2022) - Ben Abdallah, Ichrak; Berrazega, Yosra; Rachdi, Haifa; Mejri, Nesrine; Neji, Henda; Daoud, Nouha; Boussen, Hamouda
Introduction: Drug-induced acute pancreatitis (AP) is uncommon and represents 0.1 to 2% of all AP cases. Chemotherapy-induced AP is very rare. Docetaxel monotherapy-induced AP has been reported only once in the literature. Herein we report the second case of docetaxel-related AP and the first case of necrotic AP induced by this agent. Case report: We describe the case of a severe docetaxel-induced AP classified as stage E Balthazar in a 55-year-old female treated with adjuvant docetaxel for localized breast cancer. Symptoms occurred five hours following the first infusion of docetaxel. Management and outcome: The patient was hospitalized for 15 days for appropriate management. According to the CTCAE (Common Terminology Criteria for Adverse Events) version 5.0 this was a grade 4 toxicity and chemotherapy was withdrawn thereafter. Drug rechallenge was not possible because of the severity of the presentation. Discussion: Medical oncologists should be aware that docetaxel may induce severe pancreatitis. Therefore, they should prompt testing of serum lipase when patients consult for unusual abdominal pain following chemotherapy infusion. Recognizing this entity is paramount to allow early and appropriate management.